Morphometric Analysis of Lateral Masses of Axis Vertebrae in North Indians. (24th August 2014) - Lalit, Monika; Piplani, Sanjay; Kullar, J. S.; Mahajan, Anupama
Abstract : Background and Objective. The lateral masses of axis have good cancellous bone quality beneath the articular surface of facets that make this area a good site for the insertion of an internal fixation device. Methods. 60 dry axis vertebrae were obtained for anatomic evaluation focused on pedicle, superior and inferior articular facets, and foramen transversarium. Based upon linear and angular parameters the mean, range, and standard deviation were calculated. Results. The mean length, width, and height of the pedicle were 21.61 ± 2.37 mm, 8.82 ± 2.43 mm, and 5.63 ± 2.06 mm. The mean pedicle superior angle and median angle were 23.3 and 32.2 degrees. The mean superior articular facet length, width, and external and internal height were 16.34 ± 1.56 mm, 14.35 ± 1.75 mm, 8.98 ± 1.36 mm, and 4.23 ± 0.81 mm. Depth of vertebral artery was 4.72 ± 0.83 mm. Mean inferior articular facet length and width were 11.13 ± 1.43 mm and 7.89 ± 1.30 mm. The mean foramen transversarium length and width were 5.11 ± 0.91 mm and 5.06 ± 1.23 mm. Conclusions. The study may provide information for the surgeons to determine the safe site of entry and trajectory for the screw implantation and also to avoid injuries to vital structures while operating around axis.